Aplikasi Elektronik Kasir Umum E-ku Berbasis Website Metode Spiral Toko Zaynmart - Fauzi, Ahmad; Wati, Fanny Fatma; Nurohim, Galih Setiawan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
In light of the rapid technological advancements today, the utilization of the E-Ku web-based General Electronic Cashier Application remains highly relevant in aiding Micro, Small, and Medium Enterprises (UMKM) in enhancing their daily transaction efficiency. A case study for the implementation of this technology is illustrated through Zaynmart Store. The research approach adopted encompasses an analysis of Zaynmart Store's requirements and the development of web-based software accessible through a variety of devices, including computers, tablets, and smartphones. E-Ku Application empowers UMKM proprietors and their staff to effortlessly record sales transactions, manage inventory, and generate precise financial reports. Research findings underscore that the implementation of E-Ku's web-based General Electronic Cashier Application positively impacts the operational efficiency of Zaynmart Store. The streamlined transaction process facilitates time savings, reduces error potential, and enhances financial record-keeping accuracy for UMKM. Furthermore, E-Ku Application supports store owners in making informed decisions based on the data it provides. Consequently, the E-Ku web-based General Electronic Cashier Application stands as an effective tool for aiding UMKM, such as Zaynmart Store, in managing their day-to-day transactions, improving operational efficiency, and enhancing customer service. The successful implementation of E-Ku highlights the considerable potential of web technology in bolstering the growth and development of UMKM in this digital age.